2018
DOI: 10.3389/fpsyg.2018.01720
|View full text |Cite
|
Sign up to set email alerts
|

Context-Sensitivity and Individual Differences in the Derivation of Scalar Implicature

Abstract: The derivation of scalar implicatures for the quantifier some has been widely studied to investigate the computation of pragmatically enriched meanings. For example, the sentence “I found some books” carries the semantic interpretation that at least one book was found, but its interpretation is often enriched to include the implicature that not all the books were found. The implicature is argued to be more likely to arise when it is relevant for addressing a question under discussion (QUD) in the context, e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 59 publications
(142 reference statements)
2
10
0
Order By: Relevance
“…Our findings seem to converge with a recent study that did find a relationship between participants' personality traits and the proportion of scalar implicature interpretation [80]. Yang et al examined the comprehension of scalar implicatures triggered by the quantifier some in a story-sentence matching task and found that those with greater sociopragmatic abilities (as measured by the AQ) had higher sensitivity to pragmatic violations, and thus evidence that lends support to accounts arguing about the likelihood personality traits modulate the sensitivity to under-informative statements (e.g., [33,81]).…”
Section: Relationship Between Personality Traits and Rate Of Rejections Of Under-informative Sentencessupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings seem to converge with a recent study that did find a relationship between participants' personality traits and the proportion of scalar implicature interpretation [80]. Yang et al examined the comprehension of scalar implicatures triggered by the quantifier some in a story-sentence matching task and found that those with greater sociopragmatic abilities (as measured by the AQ) had higher sensitivity to pragmatic violations, and thus evidence that lends support to accounts arguing about the likelihood personality traits modulate the sensitivity to under-informative statements (e.g., [33,81]).…”
Section: Relationship Between Personality Traits and Rate Of Rejections Of Under-informative Sentencessupporting
confidence: 90%
“…Second, this study also asked the participants to judge the infelicity of the under-informative statements in an artificial context. However, a general limitation of testing some in isolation is the absence of a more natural communicative setting that provides information about whether or not the implicature is relevant, and therefore a better approach in which one can examine how individuals would interpret some in scenarios akin to everyday language situations [80,94,95]. Artificial contexts may also discourage the participants to project their own personality characteristics and their own attitudes which may in turn modulate their comprehension and interpretation of critical utterances [76].…”
Section: Discussionmentioning
confidence: 99%
“…In simple terms, it constitutes a very efficient way to enhance the scalar inference originated by some (cf. Yang et al, 2018, for a study that uses the same strategy to enhance the derivation of scalar implicatures).…”
Section: The Present Studymentioning
confidence: 99%
“…It is a robust empirical finding that B's utterance, Mary ate some of the cookies, gives rise to the familiar some but not all SI at a higher rate in (4) than in ( 5) -see i.a. Degen & Tanenhaus (2015); Ronai & Xiang (2020); Yang et al (2018); Zondervan et al (2008) for converging results. Such findings can be given an explanation along the following lines.…”
mentioning
confidence: 90%